Design of the Glass Batching-Material System Based Fuzzy-PID Combined Control - Zhisong Hou; Yanchang Liu; Qigao Feng (Institute of Advanced Engineering and Science, 2013)
According to the traditional control methods of batching-material system exists defects low precision and bad real-time, this paper has proposed the combined control algorithm. This paper has designed a Fuzzy-PID control Glass batching-material system by using of combining the traditional PID and the Fuzzy control algorithm. The system uses expert system of online learning and adjusts automatically the control parameters, realize the best combination controlling precision and speed. The actual operation result of the system has proved the feasibility and validity of the Fuzzy-PID combined control. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2689